1965
DOI: 10.1136/bmj.1.5433.480
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and its Relation to Folic-acid Status in Pregnancy: Results of a Clinical Trial

Abstract: BRITISHIsotope~~~b MEDICAL JOURNAL impression that multiple metastases are more readily shown by scanning than by pneumography or angiography. Single metastases are often revealed by these latter methods, but second or third ones are not often shown.While it is possible to predict the pathology of a certain number of lesions by studying the topography, this is by no means always so. Planiol (1963) uses an entirely different technique by means of which she is able to make a specific diagnosis in a much higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

1966
1966
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(45 citation statements)
references
References 19 publications
5
40
0
Order By: Relevance
“…Other biological deficiencies have been reported but their effects are not manifest: such is the case of folic acid deficiency [1,2], A former study on folic acid and iron status during pregnancy has. in our hands [3], confirmed the findings of other authors [4][5][6][7] with regard to folic acid defi ciency: 30% of the women at delivery had serum folic acid levels of less than 3 pg/1 and 38% had red cell folate levels of less than 150 pg/1. An observa tion of particular importance was the correlation between duration of preg nancy and maternal serum folate levels at parturition.…”
Section: Introductionsupporting
confidence: 81%
“…Other biological deficiencies have been reported but their effects are not manifest: such is the case of folic acid deficiency [1,2], A former study on folic acid and iron status during pregnancy has. in our hands [3], confirmed the findings of other authors [4][5][6][7] with regard to folic acid defi ciency: 30% of the women at delivery had serum folic acid levels of less than 3 pg/1 and 38% had red cell folate levels of less than 150 pg/1. An observa tion of particular importance was the correlation between duration of preg nancy and maternal serum folate levels at parturition.…”
Section: Introductionsupporting
confidence: 81%
“…Chanarin et al [8] reported the association of iron de® ciency with NH in 1965. Later some relevant case series were published, but in these patients IDA was usually associated with gastrointestinal diseases, such as gastritis, peptic ulcer, carcinoma, and polyp of colon, postgastrectomy [4,5].…”
Section: Discussionmentioning
confidence: 98%
“…By counting tablets prescribed, Chanarin, Rothman, and Berry (1965) concluded that on the average two out of three tablets a day were taken. Thus the results obtained in the present survey are in agreement with previous assessments.…”
Section: Discussionmentioning
confidence: 99%